Knowledge and attitude towards health and food safety among students of Tabriz University of Medical Sciences, Tabriz, Iran - Parvin Dehghan (Journal of Analytical Research in Clinical Medicine, 2017)
Introduction: Health and food safety is one of the most important issues of nutrition science. The present study aims to examine the knowledge and attitude towards health and food safety among students of Tabriz University of Medical Sciences, Tabriz, Iran. Methods: This study was conducted through cross-sectional approach on 300 students of Tabriz University of Medical Sciences who were selected through stratified random sampling method, using a validated and reliable researcher-made questionnaire. Data were analyzed by SPSS.Results: More than 50% of students had high attitude and knowledge towards health and food safety and washing hands before cooking. Further, more than 60% of students had low attitude on other related items such as unimportance of food additives in food safety. Besides, more than 50% of students had low knowledge about best temperature to store cooked food which is between 5 to 65 °C and the most appropriate plastic containers to keep food healthy. About 87.3% of students had good knowledge about diseases that could be transmitted through food. That there was a significant relationship between students' attitude and taking courses related to health and food safety (P = 0.010). There was also a significant relationship between students' knowledge and their college (P = 0.001) and major (P = 0.020). Conclusion: Results obtained revealed that students from some colleges and some majors had low knowledge of health and food safety. It is therefore necessary to hold training programs through workshops or to include courses in the curriculum of majors that lack such credits.